Quantitative assessment of bleomycin-induced poly(ADP-ribosyl)ation in human lymphocytes by immunofluorescence and image analysis - Rajaee-Behbahani, Nahid; Schmezer, Peter; Bartsch, Helmut (Journal of immunological methods, 2000)
Poly(ADP-ribose) polymerase (PARP) is a nuclear enzyme that is catalytically activated by DNA strand interruptions. It catalyses the covalent modification of proteins with ADP-ribose polymers, using NAD+ as precursor. Here, we have studied the DNA damage-induced formation of poly(ADP-ribose) in intact human peripheral blood lymphocytes (PBL) by in-situ immunofluorescence detection. The response of PBL to bleomycin (BLM), which is known to induce DNA single and double strand breaks, was investigated with regard to polymer formation. For this purpose, a quantitative approach was developed to assess more accurately the immunostaining of polymer formation by computerised image analysis. As an application of this new method, we have determined the polymer formation following BLM treatment in quiescent human PBL versus mitogen activated cells. Quiescent human PBL showed a similar basal immunostaining for the polymer compared to phytohemagglutinin (PHA)-activated cells, expressed as relative mean pixel intensity (RMPI) (1.3±0.8 and 2.2±0.9, respectively; P<0.3). After BLM treatment, there was a clear-cut enhancement of polymer immunostaining, with PHA-activated cells showing significantly higher RMPI than non-activated cells (9.2±1.4 and 4.2±1.0, respectively; P<0.005). As expected, in the presence of the ADP-ribosylation inhibitor 3-aminobenzamide (3-AB), the RMPI of immunostained polymer was decreased in both quiescent and PHA-activated PBL to 1.2±0.7 and 1.5±0.9, respectively. Our findings reveal (i) that mitogen-stimulated, intact lymphocytes show enhanced polymer formation following BLM treatment, and (ii) that our new quantitative immunofluorescence assay coupled with computerised image analysis is reliable and sensitive enough to detect changes in polymer formation rate.
Gesehen am 28.01.2021